Framing a pandemic: analysis of Malaysian mainstream newspapers in the H1N1 coverage / Chang Peng Kee, Faridah Ibrahim and Normah Mustaffa - Chang, Peng Kee; Ibrahim, Faridah; Mustaffa, Normah (CMIWS and UiTM Press, 2010)
The importance of the mass media as carriers of information especially in time of crisis, for instance war and outbreak of disease, in an epidemic or pandemic, have been discussed widely. During a crisis situation, the mass media especially the newspapers, due to their inexpensiveness and accessibility, become an important vehicle that is being sought by people to get an in-depth coverage and updates on the latest information and advice pertaining to the crisis. Since its outbreak in April 2009, H1N1 or commonly known as swine flu has become a global concern, especially among the Asian countries where medical research, facilities and medication for this disease are scarce. Like HIV/AIDS, H1N1 has become a pandemic and has been reported to reach level 6 in terms of seriousness by WHO on 11 June 2009. Using the newspapers to change the behavior of the people to adopt to the standard health procedure in order to minimize the spread of the disease has been the general practice of health practitioners and departments. In order to create awareness as well as facilitate the needs of health authorities, the newspapers through their reporters and gatekeepers will try to package the news in such a way which may benefit the target audience. Hence, various strategies including media framing have been adopted by the newspapers to impart information to the public with the hope to control or minimize the spread of the disease. This paper will focus on the findings of a content analysis based on Semetko and Valkenburg (2000) framing analysis of H1N1 pandemic in the four Malaysian mainstream newspapers namely Utusan Malaysia, New Straits Times, The Star and Berita Harian. The study also seek to find out to what extent the newspapers are involved in framing a pandemic, which is another kind of war (just like war against crime and war against drug) and whether Semetko and Valkenburg framework is workable or applicable in a pandemic situation. Furthermore, the paper will also highlight the process of prevention and intervention efforts undertaken by local authorities in managing the crisis.